COMPARATIVE LEAVES ANATOMY OF PANDANUS, FREYCINETIA AND SARARANGA (PANDANACEAE) AND THEIR DIAGNOSTIC VALUE - Yessi Santika; Eka Fatmawati Tihurua; Teguh Triono (REINWARDTIA, 2014)
Study in leaves anatomy of twenty nine samples of the species classified under Pandanus, Freycinetia and Sararanga of Pandanaceae had been undertaken to unravel generic relationship among of these taxa with a view to provide a set of diagnostic characters for taxonomic identification. The fourth genus of Pandanaceae, Benstonea is not included in this analysis since there are no representative samples. Four anatomical diagnostic characters had been identified at the generic level such as present and absent of papillae, stomatal arrangement types, present and absent of bundle sheath extension and hypodermal thickness and its shape. Pandanus has papillae, amphistomatous stomata, bundle sheath extension present and hypodermis thin and rectangular; Freycinetia lacked of papillae, stomata hypostomatous or amphistomatous, bundle sheath extension absent and hypodermis thick and hexagonal or rounded; meanwhile Sararanga has no papillae, stomata amphistomatous, bundle sheath extension absent and hypodermis thin and flatten. An identification key to those genera based on anatomical diagnostic characters is provided.